Morphology of male world cup and elite bouldering athletes - Draga, Pawel; Trybek, Paulina; Baran, Paulina; Pandurevic, Dominik; Sutor, Alexander; Grønhaug, Gudmund (Frontiers in Sports and Active Living, 2025)
AimsTo compare the somatic characteristics and somatotypes of elite bouldering athletes competing in World Cups and World Championships with national-level climbers and general adult population norms, and to identify anthropometric characteristics that differentiate performance levels in competitive climbing and distinguish climbers from the general adult population.Materials and methodsAnthropometric data were measured according to the ISAK protocol and somatotype was determined using the Heath-Carter method. Tissue composition and body proportions were examined using measurements of skinfolds, circumferences, widths and indices such as Ape Index and Arm Index. Thirty-four men participated in the study: 9 IFSC-ranked international level athletes and 25 national athletes. Statistical analysis used the Shapiro-Wilk test to assess the normality of the distribution, the Student’s t-test or Mann-Whitney U test to compare groups, LASSO regression to identify significant characteristics and Spearman’s correlation coefficient to examine correlations between variables.ResultsInternational climbers demonstrated a significantly lower body fat percentage (14.4±2.00%) compared to national athletes (17.56±2.16%) and the general adult population (18.4±2.9%). Thinner skinfolds and smaller thigh and arm girths were found among the higher level climbers. Body proportions were more favorable in international athletes, who showed higher Ape (1.06 ± 0.02) and Arm Index values (46.22 ± 1.26) compared to national-level competitors (1.03 ± 0.03 and 44.98 ± 1.45, respectively). No significant differences were observed in somatotype profiles.ConclusionsInternational climbers differ from national athletes by having higher muscle mass, lower body fat, smaller limb girths, and shorter stature. The benefits of these characteristics and the influence of selection processes remain unclear. Notably, the low body fat in elite climbers likely reflects training adaptations rather than calorie restriction.